2020
DOI: 10.2209/tdcpublication.2018-0072
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and Sleep Quality in Dental Students at a Private Brazilian University

Abstract: The aim of this cross-sectional study was to evaluate the impact of anxiety and quality of sleep on quality of life (QOL) in undergraduate dental students. A total of 141 students were enrolled. All were required to answer the following questionnaires: the State-Trait Anxiety Inventory (STAI) subscale state (S) (STAI-S); the Sleep Assessment Questionnaire (SAQ); and the simplified World Health Organization Quality of Life survey (WHO QOL-bref). The statistical analysis included univariate and bivariate analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 41 publications
1
15
0
3
Order By: Relevance
“…The State-Trait Anxiety Inventory (STAI) was used to evaluate anxiety [20]. This measure includes two subscales: State Anxiety Inventory (SAI) and Trait Anxiety Inventory (TAI).…”
Section: State-trait Anxiety Inventory (Stai)mentioning
confidence: 99%
“…The State-Trait Anxiety Inventory (STAI) was used to evaluate anxiety [20]. This measure includes two subscales: State Anxiety Inventory (SAI) and Trait Anxiety Inventory (TAI).…”
Section: State-trait Anxiety Inventory (Stai)mentioning
confidence: 99%
“…After screening of the titles and abstracts, only three full articles were found relevant. [27][28][29] The remaining 15 studies were omitted as they met the exclusion criteria or were specifically designed for disease associations. Another two full articles 30,31 was identified via searching the grey literature/hand searching providing an aggregate of five articles for comparison.…”
Section: Descriptive Data and Search Outcomesmentioning
confidence: 99%
“…Significant differences in domain scores were observed between the different year-of-study for the US, Brazilian, and Vietnamese Dental students. 27,29,31 Even though the domains involved, namely physical health, psychological, and/or environment, fluctuated among studies, the significant differences were typically observed between the first and more senior years.…”
Section: Gender and Year-of-studymentioning
confidence: 99%
See 2 more Smart Citations